2006
DOI: 10.1002/anie.200503006
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Heteroatom Active Sites in Zeolites by Hydrolysis and Inversion

Abstract: Following the discovery of the titanosilicalite zeolite TS-1 and its remarkable catalytic properties in selective oxidation reactions with aqueous H 2 O 2 , [1] there have been several reports on the possible use of other heteroatom-substituted zeolites. Of particular interest are tin and zirconium silicalites, which are efficient catalysts in the hydroxylation of phenol with aqueous H 2 O 2 .[2] Germanium-containing silicalites, as well as a number of Ti-Ge-Si zeolites, showing catalytic activity toward oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…The most detailed study addressing these problems was reported by To et al, 440,441 who used QM/MM techniques to model Ti substitutional centers in silicalite. The most detailed study addressing these problems was reported by To et al, 440,441 who used QM/MM techniques to model Ti substitutional centers in silicalite.…”
Section: View Article Onlinementioning
confidence: 99%
“…The most detailed study addressing these problems was reported by To et al, 440,441 who used QM/MM techniques to model Ti substitutional centers in silicalite. The most detailed study addressing these problems was reported by To et al, 440,441 who used QM/MM techniques to model Ti substitutional centers in silicalite.…”
Section: View Article Onlinementioning
confidence: 99%
“…Regarding the degree of complexity reached by the real catalytic systems (either at the industrial scale or the laboratory scale), it is often mandatory to go beyond the ideal surface approach at low coverage. This is particularly true when defects cannot be described by specific cleavage orientations of the bulk materials, such as for low-coordinated sites of nano-aggregates, extra-framework species or vacancies, [52][53][54][55][56][57][58][59][60][61][62] and when they dominate the surface reactivity of solids. It is also mandatory to address the complexity of the system for supported catalysts when support effects are suspected to influence directly or indirectly the reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…As already reported in ref. [26], a single inversion actually stabilizes the hydrolyzed structure. However the hydrolysis-and-inversion systems are less stable than the system in which water is bonded at the titanium site as a ligand.…”
mentioning
confidence: 96%
“…[25] Moreover, it has been reported recently that a TS-1 model with a hydrolyzed TiÀOÀSi bridge is energetically disfavoured with respect to a non-hydrolyzed TiÀOÀSi bridge plus a gas phase water molecule. [26] However, stabilization of the hydrolyzed site may occur via the so-called hydrolysis-and-inversion mechanism, [26] whereby hydrolysis of a TiÀOÀSi bridge is followed by a rotation of the titanium-centred tedrahedron (see ref. [26]).…”
mentioning
confidence: 99%
See 1 more Smart Citation